KNOWLEDGE, ATTITUDE AND PRACTICES (KAP) ON NUTRITION AMONG TRIBAL ADOLESCENT GIRLS OF KEONJHAR DISTRICT, ODISHA - VIJAYETA PRIYADARSHINI (The Journal of Research ANGRAU, 2023)
This study was conducted in the year 2021 – 22 in the Keonjhar district of Odisha, in which 45% of the population belongs to the tribal community. To assess the nutritional knowledge, attitude, and practice (KAP), 301 adolescent girls aged 16-18 were selected from the tribal-dominant blocks of Keonjhar. The study revealed that 41.2% of the respondents had average and 58.8% had poor nutritional knowledge, and the mean score was 10.8 ± 2.9.A total of 99% of the respondents had an average nutritional balanced diet practice, with a mean score of 37.7 ± 1.8 out of a maximum of 60 points. The overall nutritional practice of the tribal adolescent girls was categorised as average (mean score 9.7 ± 1.3). In the nutritional knowledge element, there was a statistically significant relationship (p < 0.05) between the respondents’ education level and Kuppuswamy’s socio-economic status of the respondents’ family. In the case of nutritional attitude and practice with Kuppuswamy’s socio-economic status, a statistically significant association was found between the education level of the respondents and the total family income of the respondents, respectively. The analysis revealed a significant difference in the nutritional practice score concerning family income and socio-economic status (p < 0.05).